Optimalisasi Pemanfaatan Aplikasi SliMS dalam Meningkatkan Kinerja Pustakawan pada Perpustakaan Institut Agama Islam Negeri Curup - Rahmat Iswanto; Eke Wince; Marleni Marleni (Institut Agama Islam Negeri (IAIN) Curup, 2019)
This paper is a theoretical study of the Optimization of the Use of SliMS applications in improving the performance and creativity of librarians in a Library. The better the performance of librarians, the better the library is managed. By using the application SliMS application many important jobs in the library that can be assisted include collections management, circulation service system, recording visit statistics, statistical collection records, database building and maintenance systems, evaluating the use of collections, and other tasks related to librarian assignments. Recording and evaluating the duties of librarians especially for the librarians of employees of Aparatur Sipil Negara (ASN) at the present time is carried out more carefully in accordance with the level and type of position. SliMS applications are well designed to accommodate all librarian tasks according to the functions of the library.